Business Process Analysis with Business Process Improvement Method Case Study: University Integrated Registration Management System - Sudana, Oka; Putra, I Made Suwija; Dewi, Pradita (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi; Vol 14 No 1 (2023): Vol. 14, No. 1 April 2023, 2023)
The university's integrated registration management system is a system to facilitate the registration of prospective new students at University X. A good registration system should be able to provide accurate, and relevant information to improve the quality of the information system. The quality improving can be done with business process analysis. In this research business process analysis is done using business process improvement methods (BPI) up to phase 3, namely streamlining. The data to be analyzed is obtained from the results of questionnaires distributed to stakeholders. Determination of quality factor indicators on questionnaire questions using the McCall framework. The questionnaire results showed a business process that is categorized as critical, namely Study Program Transfer with an average value of 80%, Quality factors categorized as critical are Correctness 80% and Integrity 51% and Scholarship Application Management with an average value of quality factor 78%, quality factors categorized critically are Correctness 80% and Integrity 53%. Recommendations for business process improvement in the form of draft Standard Operating Procedures (SOP) also flowchart using streamlining with bureaucracy elimination and upgrading simplification tools in the process of moving management program and management of waiver submissions.